Virtual learning overview of midwifery students - Evi Wahyuntari; Anjarwati Anjarwati (International Journal of Health Science and Technology, 2023)
WHO's prevention efforts against the spread of COVID-19 are to temporarily stop activities related to crowds, such as on campus so that learning that was originally done face-to-face becomes online or done remotely. This study aimed to determine the description of the implementation of virtual learning for midwifery students. The research method used a descriptive approach carried out on midwifery students at Aisyiyah University Yogyakarta, totaling 218 students in semesters 2, 4, and 6, which were carried out in May 2021 with a sample of 138 students according to the inclusion criteria. Samples taken from the D3 Midwifery study program at Universitas ‘Aisyiyah Yogyakarta semesters 2, 4, and 6 who have done virtual learning. The research instrument used a questionnaire that included basic data and the implementation of online learning. The research data were analyzed descriptively to obtain an overview of virtual learning in midwifery students. The results showed that 127 respondents (92%) agreed with online learning, 124 respondents (89.9%) disagreed with clinical practice learning carried out using online media, 138 respondents (100%) agreed that clinical practice learning during the pandemic was still carried out on the practice field by complying with health protocols. In conclusion, learning during the COVID-19 pandemic for midwifery students who need skills can be carried out by a combination of methods, namely limited face-to-face meetings and the implementation of clinical practice by complying with health protocols.